Death of a Patient Aged 2.5 Years after Infection Cause Parainfluenza Virus Type 1: A Case Report - Tecu, C.; Mihai, M. E.; Alexandrescu , V. I.; Lupulescu, E. (Research Highlights in Disease and Health Research Vol. 7, 2023)
The objective of this chapter is to show the possibility that infection with parainfluenzae virus (PIV) type 1 can causes death. Parainfluenza viruses have been linked to a variety of ailments, including otitis media, pharyngitis, conjunctivitis, croup, tracheobronchitis, and pneumonia. In this work, we disclose the discovery of parainfluenzae virus PIV 1 as the causative agent of bronchopneumonia and cardiorespiratory failure that led to the death of a 2.5-year-old child. The severity of illness is greatest in children aged 2-4 years. The patient was admitted to the hospital with a diagnosis of SARI (Severe Acute Respiratory Infection), but she died a few hours later. Laboratory tests (total WBC and differential, serum immunoglobulins, liver transaminases, urinalysis, blood sedimentation rate) were normal, and the patient had no associated disorders. We first examined the sample (a right lung fragment) for the presence of influenza viruses A and B (including pandemic H1N1) because the patient became unwell during the 2009-2010 pandemic season. Following the negative discovery of influenza viruses, we analyzed the sample for the existence of other respiratory viruses. At the same time, we looked to see if the samples had respiratory bacteria. The Real-time PCR method for detection of A/H1N1 pandemic virus and the Reverse Transcription-Polymerase Chain Reaction (RT-PCR) for detection of other non-influenza viruses (respiratory syncytial virus, human metapneumo virus, PIV 1, 2 and 3, Coronaviruses 229E and OC43) were used as diagnostic methods. In addition, the probable bacterial etiology of the infection (Streptococcus pneumoniae, Haemophilus influenzae, Legionella pneumophila, Mycoplasma pneumoniae, and Chlamydophila pneumoniae) was tested using the Kit RV/PB18 ASE Detection (Seegene). The study found that even though the patient had no history of chronic illnesses, she died from bronchopneumonia caused by PIV type 1.